Intergrasi Fiqih dalam Kurikulum Modern: Menjembatani Tradisi dan Teknologi - Septi Wulandari; Sofia Dzatil Izah; Rohadatul Aisy; Riska Maulita; Imam Tauhid (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Technological progress in education has significantly transformed teaching methods, learning approaches, and academic objectives. Amid these rapid changes, figh as a core discipline in Islamic education faces challenges in maintaining its relevance and significance. This article examines the integration of figh into the modern curriculum, focusing on how Islamic scholarly traditions can be linked with the aduancement of educational technology. Using a descriptive qualitative approach and literature analysis, this study reveals that integrating figh into contemporary learning requires not only methodological adaptation but also a reinterpretation of how Islamic legal values are conveyed within a digital context. Technology serves as a strategic medium to enrich the learning experience, while tradition offers the ethical and spiritual foundation that guides learners. Therefore, integrating figh into the modern curriculum is essential for developing comprehensive, relevant, and sustainable Islamic education in the digital era.